Different nest predator guild associated with egg size in the Patagonian temperate forest - Vazquez, Miriam Soledad (2018)
Capsule: Studies of nest predation using artificial nests need to consider the effect of egg size on the types of predator that are detected. Aims: To estimate the nest predation rate in the Patagonian temperate forest and evaluate the influence of egg size on predator guild. Methods: On different plant species, we placed 108 nests each containing eggs of either Atlantic Canary Serinus canaria or Common Quail Coturnix coturnix, and a model clay egg of equal size to the real egg. Nest predators were identified from the marks left on the clay eggs or by videos recorded using camera traps. Results: 86% of the nests were predated. Birds, mainly Chimango Caracara Milvago chimango, were the main nest predators. A marsupial, the Monito del Monte Dromiciops gliroides, and rodents also contributed to nest predation. Nest predation rates were similar for both egg sizes but the nest predator guild was different. Birds and rodents preyed on both eggs but the Monito del Monte consumed mainly small eggs. Conclusion: Egg size did not influence the rate of nest predation but, instead, affected the nest predator guild. Consequently, in order to avoid underestimating the impacts of small predators, egg size should be considered in studies of nest predation.